When the expression x-1 is substituted into the first equation for y, what is the resulting equation when given #3x-y=2, y=x-1#?

1 Answer
Nov 29, 2016

Answer:

#x=3/2#
Every step shown. As you become more confident with this type of question you will start to jump steps and become much faster at solving them.

Explanation:

Given:

#" "y=x-1" "...................Equation(1)#
#3x-y=2" "....................Equation(2)#
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
Using equation(1) substitute for #y# in equation(2)

#color(green)(3xcolor(red)(-y)=2" "->" "3xcolor(red)(-(x-1))=2#

#3x-x+1=2#

but #3x-x=2x#

#2x-1=2#

Add 1 to both sides

#2x-1+1=2+1#

#2x+0=3#

#2x=3#

Divide both sides by 2

#2/2xx x=3/2#

But #2/2=1#

#x=3/2#